2017
DOI: 10.1093/nar/gkx427
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cyclobutane thymine photodimer formation in T11-tracts in rotationally phased nucleosome core particles and DNA minicircles

Abstract: Cyclobutane pyrimidine dimers (CPDs) are DNA photoproducts linked to skin cancer, whose mutagenicity depends in part on their frequency of formation and deamination. Nucleosomes modulate CPD formation, favoring outside facing sites and disfavoring inward facing sites. A similar pattern of CPD formation in protein-free DNA loops suggests that DNA bending causes the modulation in nucleosomes. To systematically study the cause and effect of nucleosome structure on CPD formation and deamination, we have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The variable reactivity of 5fCs in NCPs probably owe to their different exposure and proximity to the histone tails. This is consistent with previous observations that demonstrated that even slight changes in rotational positioning can affect the DNA damage reactivity in NCPs. …”
supporting
confidence: 93%
“…The variable reactivity of 5fCs in NCPs probably owe to their different exposure and proximity to the histone tails. This is consistent with previous observations that demonstrated that even slight changes in rotational positioning can affect the DNA damage reactivity in NCPs. …”
supporting
confidence: 93%
“…It is known that superhelical location and rotational orientation significantly impact damaged DNA reactivity in NCPs. , Herein, NCP-8-oxodGuo 73 /C and NCP-8-oxodGuo 137 /C were employed for addressing the effect of 8-oxodGuo location and orientation on DPC formation. The yield (48%) of 8-oxodGuo oxidation in NCP-8-oxodGuo 73 /C was higher than that of NCP-8-oxodGuo 89 /C (31%).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the yield of CPDs is lower in the nucleosome than in the linker region 156,157 . A recent work provided accurate information on the favored locations of CPDs within a rotationally phased nucleosome 158 . The ratio between 64PPs and CPDs is also affected by the nucleosome structure 159 .…”
Section: Formation Of Pyrimidine Dimers In Cells and Skinmentioning
confidence: 99%